Pengaruh Kegiatan Ecoprint untuk Mengembangkan Kreativitas Anak di PAUD Ceria Kubu Raya - Nurhaliza, Nurhaliza; Miranda, Dian; Perdina, Siska (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of ecoprint activities on developing children's creativity at PAUD Ceria Kubu Raya. This research uses a quantitative method in the form of an experiment with a pre-experimental research design of one-group pretest-posttest. The number of samples in this study is 30 children. The data collection techniques used in this study are observation sheets, checklists, and documentation. The data analysis techniques used are normality test and t-test. The results show that the average creativity score of children in the pretest is 48.3 (medium category), while the average score in the posttest increased to 88.95 (very high category). The t-test shows a significance value of p = 0.000 < 0.05, thus the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This research shows that ecoprint activities can be an enjoyable, creative, and environmentally friendly alternative for art education in early childhood education (PAUD). Teachers can utilize it to stimulate children's imagination and creativity, parents can support similar activities at home, and educational institutions can adopt it as an innovative learning method that aligns with the PAUD curriculum. It can be concluded that batik activities through ecoprint techniques have an impact on the development of children's creativity at PAUD Ceria Kubu Raya.